Techno-Economic Analysis of Biorefinery from Oil Palm Frond Petiole for Bioethanol and Electricity Production in Indonesia - Shabrina, Aulia; Koji Tokimatsu (Jurnal Serambi Engineering, 2026)
Indonesia faces challenges in increasing the share of renewable energy, while large amounts of oil palm biomass remain underutilized. Oil palm frond (OPF) petiole is an abundant non-food residue with strong potential as a feedstock for bioethanol-based biorefineries. This study aims to evaluate the techno-economic feasibility of OPF petiole utilization by comparing three biorefinery configurations integrated with an existing palm oil mill processing 45 tons of fresh fruit bunches per hour. The assessment was conducted through process modelling, mass and energy balance analysis, and economic evaluation. Scenario 1 utilizes OPF juice to produce first-generation ethanol, and the remaining bagasse is burnt for electricity. In Scenario 2, both OPF juice and saccharified bagasse are converted to first- and second-generation ethanol through Separate Hydrolysis and Fermentation (SHF). Scenario 3 combines alkaline pretreatment and Simultaneous Saccharification and Fermentation (SSF). The residual fiber in all scenarios is used as solid fuel in the cogeneration system. The results show that Scenario 3 provides the highest ethanol yield at 9.65 million L/year. Although this scenario requires more external electricity than the other scenarios, it provides the most profitable pathway with an ROI of 7.91%, IRR of 14.93%, NPV of 24.97 million USD, and POT of 5.58 years. Thus, the SSF conversion of OPF petiole is identified as the most attractive scheme to optimize the palm oil biorefinery system in Indonesia.